Alterações maiores do eletrocardiograma na população brasileira: valor prognóstico e determinantes de incidência - Estudo Longitudinal de Saúde do Adulto (ELSA-Brasil) - Marcelo Martins Pinto Filho (2020)
BACKGROUND: Cardiovascular diseases (CVD) are the main cause of morbimortality worldwide. The electrocardiogram (ECG) is a low-cost, widely available and frequently used diagnostic tool in the care of the patient with cardiovascular complaints. Nevertheless, its role in determining CVD prognosis as well as in the screening for CVD is still unclear. METHODS: This is a cohort, study with data from 13428 adults (45% men, age 35-74 years old) from the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil), which included the ECG, coded according to the Minnesota Coding System (MC). Its main goal is to evaluate the prognostic impact of major electrocardiographic abnormalities (MEA) according to the MC. Mortality was analyzed through Kaplan-Meier curves and compared by the log rank test. Adjustment for cardiovascular and sociodemographic risk factors were made by Cox regression. Cardiovascular mortality risk was evaluated by the Fine and Gray competitive risk model. We also evaluated the potential of MEA in reclassifying the participants’ cardiovascular mortality risk calculated by the Systematic Coronary Risk Evaluation (SCORE) using the net reclassification index. After a four-year follow up, new ECG data was obtained and the incidence of new MEA was measured with its possible determinants evaluated. This particular analysis was stratified by sex. RESULTS: Participants with baseline MEA were in general of higher CVD risk. After multivariable analysis, the presence of MEA was still an independent predictor of total mortality (HR 2.3, 95% CI 1.7-2.9) and cardiovascular mortality (HR 4.6 IC 95% 3.0-7.0). Among the MEA analyzed, major ST-T abnormalities, intraventricular blocks and major QT interval prolongation were the most relevant. In adding MEA to the SCORE risk prediction tool, we were able to accurately reclassify 15% of intermediate risk individuals to a high-risk stratum. In the other hand among survivors, 3% were miss-reclassified from intermediate to a high-risk category. In a four-year follow up, the incidence of MEA was similar between men and women without prevalent CVD or MEA (10.9% and 11.1% respectively). For this short period we were not able to identify any predictors for incident MEA. CONCLUSIONS: The presence of major electrocardiographic abnormalities according to the Minnesota coding system, were independent predictors of general and cardiovascular mortality in the studied population. We achieved a favorable net reclassification index for the participants within the intermediate risk category. Incident MEA in four years was high, even though no clinical predictors were identified.